Liver Tumor Characterization – Review of the Literature - Dietrich, C. F.; Maddalena, M. E.; Cui, X. W.; Schreiber-Dietrich, D.; Ignee, A. (Ultraschall in der Medizin - European Journal of Ultrasound, 2012)
Multicenter trials to assess contrast-enhanced ultrasound (CEUS) for the imaging of focal liver lesions (FLLs) have included more than 1000 patients. This article reviews the published literature pertaining to these trials to determine the role of CEUS in the characterization of FLL.
Keywords: diagnosis; characterization; metastases; hepatocellular carcinoma; guidelines; hemangioma; microbubble contrast agent